SELEKSI HABITAT OLEH REKREKAN (Presbytis fredericae Sody, 1930) DI TAMAN NASIONAL GUNUNG MERBABU - , Syarifah ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research describes the habitat selection by rekrekan (Presbytis fredericae Sody, 1930) in Merbabu National Park (MNP). Rekrekan was selected as the research object because instead of its important role in ecology that affects forest regeneration patterns and diversity of tree species in the habitat, rekrekan become one of the endemic species in Central Java that was endangered and in the brink of extinction. This study become interesting to be learned because the species can only be found in spesific location of the MNP. The purpose of this research was to investigates the habitat selection by rekrekan in MNP, to learn the characters of the vegetation in the type of habitat that selected by rekrekan, to find out biotic and abiotic components that was affect habitat selection by rekrekan, and to find out the characteristics in microsite level of the habitat that was chosen by rekrekan in MNP. Chi-square test used to know existence of habitat selection, and logistic regression test used to predict the variables that affect the probability of the rekrekan presence. Study of habitat selection by rekrekan was conducted for three months, from April to Juni 2013. Chi-square showed that there was a habitat selection by rekrekan in MNP. Characteristic of the habitat selected by rekrekan were having abundant of fodder trees (160 trees/ha), its canopy have a high percentage of coverage (81,52%), and on the position altitude is in between 1.951 â 1.515 meters asl. These habitat characteristics were Type II habitat in study area. Base on logistic regression analysis, probability of rekrekan presence increasing along with the increase of fodder tress number, percentage of canopy coverage, and the altitude.